Priority General Authorisations in rights-based water use authorisation in South Africa - van Koppen, Barbara; Schreiner, B. (IWA Publishing, 2014)
This article unravels the notions of justice in statutory water law in Sub-Saharan Africa in general and South Africa in particular. These laws, which allocate and regulate water resources, are licence (or permit) systems. Three forms of injustices are identified for small-scale water users who typically encompass all poor water users: the reinforcement of the historical injustices by which colonial powers captured ownership of water resources and undermined customary water law; administrative discrimination as a result of governments’ lack of capacity to license the large numbers of small-scale users; and discrimination of the smallest-scale users whose exemption from the obligation to apply for a licence relegates them to a second-class entitlement to water. Based on the texts and implementation experiences of the National Water Act (1998) and the pro-poor prioritisation rules in the National Water Resource Strategy-2 (2013), the authors propose the transformative legal tool of priority General Authorisations for black small-scale users to overcome these injustices. Via this tool all black small-scale users, including the poor, would obtain equal access to minimum quantities of water needed to progressively achieve constitutional rights to water, food, and non-discrimination, while the remaining water resources would be allocated to high-impact users through licences with strict and enforceable conditions.